Studi Literatur Review Pengembangan Media Pembelajaran Menggunakan Aplikasi Thunkable di Sekolah Dasar - Arlangga Ridho Aruliansyah; Ayun Nafi’ah Rhesnandya Surya; Zalsita Prasasti Putri; Findya Merliana; Fida Rahmantika Hadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The continuous advancement of technology affects the education sector, especially through the emergence of new media that increasingly use digital technology, commonly called e-learning. One prominent example is the use of Android-based educational media via mobile phones, which are designed to operate under explicit guidelines that enhance students' learning experiences. The media used in educational activities function as a channel for transmitting information, thus facilitating the understanding of learning materials and increasing the success of achieving educational goals. After achieving learning objectives, a student is given a certification that lists their name, achievements, and behavioral modifications. The importance of media literacy is essential for students in obtaining instructions and knowledge from their educators, which ultimately results in a deeper understanding of the subject matter. This investigation aims to determine, based on the main findings, the suitability and benefits of this media for elementary school students. The research method used is the Systematic Literature Review (SLR), with articles taken from several sources such as Google Scholar.